PENGARUH PEMAMFAATAN FABA (FLY ASH AND BOTTOM ASH) TERHADAP LAJU PERPINDAHAN PANAS PADA TUNGKU ARANG - Afandi, Afandi; Salimin, Salimin; Delly, Jenny (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2018)
As a manifestation of the application of materials engineering science in the field of furnace experimentalresearch makes a study to solve the problem what happens to the existing stove by utilizing the material thatis cheap and easy to get and applied in this case the materials used are faba (flyash and bottom ash) as amedia insulator that can increase the head resistance of the clay furnace, as previous research has shown flyash can be used as an.This experimental study was conducted on five different model variations ofcomposition . the materials used are clay cement, sand and fly ash. The data obtained is measured by the toolthermo coople. The results of this study indicate that the material on the composition 40:60% lowestconductivity value is obtained0.018 W/m.oC with the head provided ±500 oC.the lower the conductivity valuethe better the quality of the material as the insulator.Keyword: Composite, conductivity, faba, fly ash and bottom ash.